Iodine Deficiency during Preconception Period of Adolescent Girls Residing in a District of Rajasthan, India - Vijay, Jyoti (Indian J Community Med, 2020)
BACKGROUND: In India, iodine deficiency (ID) still remains a serious concern even after five decades of enormous efforts. ID during the preconception period of adolescent girls may negatively affect future neonates, resulting in neonatal hypothyroidism. Hence, the present study was conducted to assess the prevalence of goiter and associated factors among adolescent girls in a poor socioeconomic district of Rajasthan. METHODOLOGY: A cross-sectional study was conducted during January–March 2015 in Tonk district of Rajasthan. A total of 1912 adolescent girls were selected from thirty schools using population proportionate to size sampling. Adolescent girls were clinically examined for thyroid using palpation method. Casual urine (n = 344) and salt samples (n = 370) were collected from a subgroup of girls for the estimation of urinary iodine concentration (UIC) and iodine content in salt, respectively. RESULTS: The overall goiter prevalence was 15.3% (95% confidence interval 13.6%–16.9%) and the median UIC was 266 μg/l (interquartile range: 150–300 μg/l) among 1912 adolescent girls (age, 15.7 ± 1.4 years). Around 16.8% of the families of adolescent girls were consuming salt with inadequate iodine (<15 ppm). Goiter prevalence was statistically significantly different with respect to age groups (P = 0.03). There was no statistically significant difference in goiter prevalence with respect to iodine content of salt (P = 0.98) and UIC (P = 0.41). The median UIC increased with an increase in consumption of iodine content of salt from inadequacy to adequacy (P = 0.15). CONCLUSION: Adolescent girls, residing in an underdeveloped district, are in the transition phase from mild ID (goiter prevalence 15.3%) to iodine sufficiency (median UIC 266 μg/l).